Supervisory Role Of Regional Assembly (Mpd) On Notary Monitoring In Leaving The Area Without Legal Reasoning Which More Than 7 (Seven) Working Days In Banjarnegara - Alfian Ridho Chusosi; Carlito Da Costa; Munsharif Abdul Chalim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
In the Constitution of the State in 1945 expressly stated that the Republic of Indonesia is legal state, is thus one of the most important tasks for the government is provide and ensure a sense of legal certainty for the citizens of the community members. In certain fields this task by the government through the Law given and entrusted to the Notary and vice versa community must also believe that the Agreement made that provides legal certainty for citizens, in accordance with the wording of Article 15 paragraph 1 of Act No. 30 of 2004 jo Act No. 2 of 2014 concerning Notary. The legal certainty in addition to the authenticity of a certificate that has the strength of evidence, ie outwardly, formal and material as well as the ethics of a Public Notary in the running position. In carrying out the duties of office of the Notary not only carry out the work mandated by legislation alone as well as running a social function that is very important is to be responsible for carrying out the trust placed in the general population it serves, Notary authorized to make the authentic act on all agreements, agreements and statutes required by the rules and regulations and / or desired by the stakeholders to be stated in an authentic agreement, agreement of guarantee certainty of the date of manufacture, save agreement, giving grosse, copy, and official copies.Keywords: Public Notary, Regional Assembly, Legal Reasoning